The Role of Organizational Culture, Knowledge Sharing, and Innovation Capability on Firm Performance - Tri Cicik Wijayanti; Nur Faliza; Rahmat Ramdhani; Sarlianus Poma (Journal Management & Economics Review (JUMPER), 2026)
In the modern business environment, organizations must effectively manage internal resources such as organizational culture, knowledge, and innovation in order to enhance firm performance and maintain competitiveness. This study aims to examine the role of organizational culture, knowledge sharing, and innovation capability in influencing firm performance. A quantitative research approach was employed using a cross-sectional survey design. Data were collected from 200 employees and managers working in various organizations through a structured questionnaire using a five-point Likert scale. The data were analyzed using descriptive statistics, reliability testing, correlation analysis, and multiple regression analysis. The results indicate that organizational culture has a positive and significant effect on firm performance, suggesting that a supportive organizational environment encourages collaboration and improves organizational outcomes. Knowledge sharing also demonstrates a significant positive influence on firm performance by facilitating the exchange of information, expertise, and experiences among employees, which enhances organizational learning and decision-making. Furthermore, innovation capability shows the strongest positive effect on firm performance, indicating that organizations with strong innovation capabilities are better able to develop new ideas, products, and processes that contribute to competitive advantage. The findings highlight the importance of integrating organizational culture, knowledge sharing practices, and innovation capability to improve overall organizational performance. This study provides theoretical and managerial implications by emphasizing the role of intangible organizational resources in driving firm performance and sustaining long-term competitiveness in dynamic business environments.